Intrusion and extrusion of a liquid on nanostructured surfaces. (10th November 2016) - Amabili, M; Giacomello, A; Meloni, S; Casciola, C M
Abstract: Superhydrophobicity is connected to the presence of gas pockets within surface asperities. Upon increasing the pressure this 'suspended' state may collapse, causing the complete wetting of the rough surface. In order to quantitatively characterize this process on nanostructured surfaces, we perform rare-event atomistic simulations at different pressures and for several texture geometries. Such an approach allows us to identify for each pressure the stable and metastable states and the free energy barriers separating them. Results show that, by starting from the superhydrophobic state and increasing the pressure, the suspended state abruptly collapses at a critical intrusion pressure. If the pressure is subsequently decreased, the system remains trapped in the metastable state corresponding to the wet surface. The liquid can be extruded from the nanostructures only at very negative pressures, by reaching the critical extrusion pressure (spinodal for the confined liquid). The intrusion and extrusion curves form a hysteresis cycle determined by the large free energy barriers separating the suspended and wet states. These barriers, which grow very quickly for pressures departing from the intrusion/extrusion pressure, are shown to strongly depend on the texture geometry.